Figma: Website-based Interactive Learning Media to Train Understanding of The Concept of Plant Body Part Functions for Elementary Students - Rohmah, Siti; Irianto, Dede Margo; Kurniawan, Dede Trie (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This study aims to develop interactive learning media based on figma website for grade IV elementary school and analyze students' concept understanding. The method used in this research is D&D Type II with 6 stages of peffers model and one group pretest posttest design. The participants in this study involved 38 students of class IV of one of the elementary schools in Bandung city. The data obtained in this study are data from material expert validation results of 98%, media experts 79%, language experts 94%, elementary learning experts 97.5%, so that an average value of 92.13% is obtained with a very feasible category. The data on the value of teacher user response is 93%, and the average value of student response is 89.5% with a very feasible category and get a positive response to interactive media. The results of the N-Gain data analysis of students' pretest concept understanding scores were 43.42 and the posttest N-Gain was 78.94. The data shows that the interactive learning media developed can train students' concept understanding on the material of the function of plant body parts.